2000
DOI: 10.1046/j.1365-313x.2000.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, functional expression and characterisation of RCC reductase involved in chlorophyll catabolism

Abstract: SummaryRed chlorophyll catabolite (RCC) reductase (RCCR) and pheophorbide (Pheide) a oxygenase (PaO) catalyse the key reaction of chlorophyll catabolism, porphyrin macrocycle cleavage of Pheide a to a primary¯uorescent catabolite (pFCC). RCCR was puri®ed from barley and a partial gene sequence was cloned (pHvRCCR). The gene was expressed at all stages of leaf development and in roots. By comparison with different databases, genomic sequences and expressed sequence tags similar to RCCR were found in phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 19 publications
4
154
0
5
Order By: Relevance
“…However, the subchloroplast location of respective reactions remained largely unclear until recently, in particular because of the inconsistency with regard to the presence or absence of transmembrane domains in these proteins. Thus, for example, PAO is an integral membrane protein with two predicted transmembrane domains ( Figure 5A) (Sakuraba et al, 2012), while RCCR, with which it physically interacts during catalysis (Rodoni et al, 1997;Pruzinská et al, 2007), is a soluble protein (Wüthrich et al, 2000). Recently, based on protein interaction studies, we proposed the model that all chloroplastlocated chlorophyll catabolic enzymes form a highly dynamic multiprotein complex at the thylakoid membrane with interaction with light harvesting complex II proteins (Sakuraba et al, 2012).…”
Section: Spatial Distribution Of Chlorophyll Catabolic Enzymes Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the subchloroplast location of respective reactions remained largely unclear until recently, in particular because of the inconsistency with regard to the presence or absence of transmembrane domains in these proteins. Thus, for example, PAO is an integral membrane protein with two predicted transmembrane domains ( Figure 5A) (Sakuraba et al, 2012), while RCCR, with which it physically interacts during catalysis (Rodoni et al, 1997;Pruzinská et al, 2007), is a soluble protein (Wüthrich et al, 2000). Recently, based on protein interaction studies, we proposed the model that all chloroplastlocated chlorophyll catabolic enzymes form a highly dynamic multiprotein complex at the thylakoid membrane with interaction with light harvesting complex II proteins (Sakuraba et al, 2012).…”
Section: Spatial Distribution Of Chlorophyll Catabolic Enzymes Withinmentioning
confidence: 99%
“…PAO, in concert with red chlorophyll catabolite reductase (RCCR), catalyzes the ring-opening reaction of pheophorbide a, the phytol-and Mg-free intermediate of the early part of chlorophyll breakdown, to a primary fluorescent chlorophyll catabolite (pFCC), the primary (fluorescent) phyllobilin that is the precursor of all subsequently formed phyllobilins. The direct product of the PAO reaction, red chlorophyll catabolite, does not accumulate but is immediately reduced at the C15/C16-double bond by RCCR in an intriguing stereospecific manner (Wüthrich et al, 2000;Pruzinská et al, 2007) (for atom and pyrrole numbering of phyllobilins, see the structure of pFCC in Figure 1B). Thus, depending on the source of the enzyme, two C16-stereoisomers, pFCC or epi-pFCC, may occur (Mühlecker et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…RCCR was molecularly identified more than ten years ago (Wüthrich et al 2000) and was shown to be identical to ACD2 (Greenberg et al 1994;Mach et al 2001). acd2 mutants develop a cell death phenotype which highly correlates with the accumulation of RCC and RCC-like pigments (Pružinská et al 2007).…”
Section: Red Chlorophyll Catabolite Reductasementioning
confidence: 99%
“…RCCR was experimentally shown to localize to the chloroplast (Wüthrich et al 2000), but it also partially localizes to mitochondria, particularly upon stresses, such as pathogen infection or protoporphyrin IX treatment (Yao and Greenberg 2006). In addition, cell death in acd2 involves an early mitochondrial oxidative burst (Yao et al 2004).…”
Section: Red Chlorophyll Catabolite Reductasementioning
confidence: 99%
“…The opening of the Pheide a macrocycle by PaO produces a red colored catabolite (RCC), an intermediary product, which in turn is reduced by RCCR in a reaction requiring ferredoxin to form pFCC, a colorless compound that is detected by its distinctive blue fluorescence (Wü thrich et al, 2000). The RCCR gene is expressed in most tissues, even roots (Mach et al, 2001;Yao and Greenberg, 2006), and is constitutively active throughout leaf development, including senescence.…”
mentioning
confidence: 99%